1998
DOI: 10.1002/hlca.19980810116
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of (S)‐5,5,5,5′,5′,5′,5′‐Hexafluoroleucine

Abstract: S)-5.5,5,5',5',5'-Hexafluoroleucine ((S)-13) of 81 YO ee is prepared from hexafluoroacetone (1) and ethyl bromopyruvate (= ethyl 2-oxopropanoate) in 7 steps with an overall yield of 18% (Schemes f and 2). Key step in this sequence is the highly enantioselect~ve reduction of the carbonyl group in cc-keto ester 4 either by bakers' yeast (91 % ee) or by 'catecholborane' 6 utilizing an oxaraborolidine catalyst, yielding hydroxy ester (R)-5 with 99 %, ee. The absolute configuration was determined by X-ray analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
(6 reference statements)
1
20
1
Order By: Relevance
“…Since size and hydrophobicity are known to be essential factors for secondary structure formation, we compared 5-F 3 Ile with previously studied (2 S ,3 S )-4’-F 3 Ile [13], as well as with ( S )-5,5,5,5’,5’,5’-hexafluoroleucine (F 6 Leu), which was prepared according to procedures reported by Keese and coworkers [25]. …”
Section: Resultsmentioning
confidence: 99%
“…Since size and hydrophobicity are known to be essential factors for secondary structure formation, we compared 5-F 3 Ile with previously studied (2 S ,3 S )-4’-F 3 Ile [13], as well as with ( S )-5,5,5,5’,5’,5’-hexafluoroleucine (F 6 Leu), which was prepared according to procedures reported by Keese and coworkers [25]. …”
Section: Resultsmentioning
confidence: 99%
“…Although various procedures for synthesizing (S)-5,5,5,5Ј,5Ј,5Ј-hexafluoroleucine (Hfl) have been reported, [40][41][42][43] the development of new methodologies to prepare its fluorinated analogues with more favorable helix propensities remains intensive and challenging because research demonstrated that these helix propensities were drastically reduced upon replacement of Leu with Hfl. In 2007, Scheme 14. Cheng and Chiu developed short chemoenzymatic syntheses both of (S)-Hfl (137, Scheme 15) and of (S)-5,5,5Ј,5Ј-tetrafluoroleucine (Qfl, 138) on gram scales.…”
Section: Trifluorinated and Perfluorinated α-Amino Acidsmentioning
confidence: 99%
“…After 2 h, the solid was filtered off to give 7.7 g (59%) of 6d, containing 3% of 6c (NMR). The N-acylation of 7b · HCl with (À)-(S)-Moshers acid chloride was performed as described for the acylation of 7a · HCl with (þ)-(R)-Moshers acid chloride [8].…”
Section: Experimental Partmentioning
confidence: 99%
“…The ready access to chiral hexafluorovaline is based on the observation by Knunjants et al [3a] that b,b-bis(trifluoromethyl)acrylate reacts with NH 3 in the a-position of the C¼C bond. Hexafluoroacetone was used as the starting material for our preparation of (S)-5,5,5,5',5',5'-hexafluoroleucine [8].…”
mentioning
confidence: 99%